ULTRASTRUCTURE OF MYOCARDIAL BLOOD CAPILLARY ENDOTHELIAL CELLS IN YOUNG RATS WITH ALIMENTARY OBESITY ON BACKGROUND OF APPLYING THE CRYOPRESERVED CORD BLOOD PREPARATION - Chernyavskaya, E.A.; Nevzorov, V.P.; Babiychuk, V.G.; Martynova, Yu.V.; Kulik, V.V. (World of Medicine and Biology, 2015)
In the electron microscopic study of myocardium blood capillary endotheliocytes of rats with alimentary obesity on the background of introduced cryopreserved preparation of cord blood nucleated cells it has been shown that young experimental animals with simulated alimentary obesity, compared with intact control, there are developed the marked dystrophic and destructive disorders in submicroscopic architecture of endothelial cells. In more distant periods of the experiments in endothelial cells the reparative changes of organelles continued to develop and the activity of intracellular metabolic processes increased. The experimental data obtained in future will provide an opportunity to compare the dynamics of ultrastructural rearrangements of myocardium blood capillary endothelial cells of young and aged rats with obesity after application of cord blood nucleated cells.
Keywords: alimentary obesity; cord blood nucleated cells; endothelial cells; mitochondria; rats